Cryptocurrency as a New Object of Forensic Economic - M. M. Vinogradova (Теория и практика судебной экспертизы, 2024)
The article examines a new object of forensic economic examination – cryptocurrency. The author provides classic definitions of an object of forensic examination and establish the differences of cryptocurrency from the traditionally understood objects of both forensic examination in general and economic examination in particular. The main difference of cryptocurrency from other currencies and objects of investigation is its virtual nature, lack of affiliation with the material world. Two main points of view on the essence of cryptocurrency are analyzed: as a basis and tool for the development of new effective forms of payments, exchange of goods, and as an object and instrument of criminal activity. A definition of cryptocurrency is given as interpreted by the FATF – Financial Action Task Force. It is identified which issues related to the circulation of cryptocurrency can be attributed to the competence of a forensic expert-economist, and which – to the field of computer forensics. The author also describes the features of cryptocurrency that must be taken into account when considering it as an object of forensic economic examination.